Application of the modified pitman and swat models for groundwater recharge estimation in the upstream area of the Uitenhage artesian basin, South Africa - Wasswa, Peter (Rhodes University, Faculty of Science, Institute for Water Research)
The world's most plentiful source of freshwater is thought to be groundwater. During extended dry times, it serves as an essential storage component and guards against environmental catastrophes. Despite its critical functions in the aforementioned scenarios, it is often insufficiently understood and inadequately managed. As a result, it calls for the adoption of integrated methods to comprehend the dynamics of groundwater recharge. Thus, the current study evaluated the applicability and suitability of the Modified Pitman and SWAT models for groundwater recharge estimation in the upstream area of UAB for the period that spanned from 1993 to 2021. It was achieved by using a qualitative conceptual-perceptual model to inform the two hydrological models, Modified Pitman, and SWAT. The developed qualitative conceptual-perceptual model depicted the dominancy of irregularly folded and fractured TMG rock outcrops coupled with fault systems in the upstream area. In the downward section, TMG is overlaid by the aquiclude from the Uitenhage Group which is responsible for the artesian conditions. Groundwater potential zones were classified as Poor, Fair, Good, and Excellent, with 65.4% and 8.7% of the upstream area attributed to Good and Excellent zones respectively. Both Modified Pitman and SWAT predicted decreasing rates of groundwater recharge in the upstream area over time, though Mann-Kendal trend tests done at 5% signifance level depicted significant decreasing rates in SWAT predicted recharge compared to Modified Pitman predicted recharge. The two models did also predict recharge and other water balance components with differing peaks, lows and timings. Modified Pitman predicted mean annual recharge of 63.3-92.8 mm where as SWAT predicted mean annual recharge of 14.4-182.8 mm. In reference to earlier findings within TMG areas, estimated percentages of groundwater recharge were close to those simulated by both Pitman and SWAT models. Modified Pitman and SWAT models appear to both be reasonable tools to estimate recharge in TMG setting, producing relatively similar results to one another and to other regional estimates. Since the current study estimated low recharge rates (Modified Pitman; ~9.3-13.6% MAP), (SWAT; ~2.1-26.7% MAP) which are close to those predicted in other TMG areas, the study recommends exercising caution when developing a water supply strategy in the current study area. The recharge rates within the pertinent recharging areas should be considered when designing and sitting abstraction points such as boreholes and a sustainable abstraction rate in any one borehole for improved sustainable management of groundwater resources.
Keywords: Hydrologic models; Groundwater recharge; Runoff Mathematical models; Rain and rainfall Mathematical models; Water-supply Management; Artesian basins -- South Africa -- Eastern Cape